Gorlin-Goltz syndrome - Şereflican, Betül (Turk Pediatri Ars, 2017)
Gorlin-Goltz syndrome is a rare multisystemic disease inherited in an autosomal dominant pattern. It is characterized by numerous basal cell carcinoma of the skin, jaw cysts, and skeletal anomalies such as frontal bossing, vertebral anomalies, palmoplantar pits, and falx cerebri calcification. There is a tendency to tumors including medullablastoma, fibroma, rabdomyoma, leiomyosarcoma etc.. The diagnosis is based on major and minor clinical and radiologic criteria. Early diagnosis and treatment are of utmost importance in reducing the severity of long-term sequelae of this syndrome. In this article, we present a 15-year-old boy who was admitted to our clinic with brown-black papules and plaques on his scalp and was thought to have Gorlin-Goltz syndrome. He had a history of medulloblastoma that was treated with surgical resection followed by cranial radiotherapy and unilateral retinoblastoma. We present this case, because association of Gorlin-Goltz syndrome and retinoblastoma has not been described previously in the literature and we aimed to draw attention to radiation-induced basal cell carcinomas.